Influence of Audit Opinion, Cap Size, Financial Distress, and Company Size on Auditor Switching: (Empirical Study of Manufacturing Companies in Various Industrial Sectors Listed on The Indonesian Stock Exchange for the 2019-2022 Period). - Rina Rina; Sigit Mareta (Dinasti Publisher, 2024)
This study aims to examine the influence of Auditor Opinion, KAP Size, Financial Difficulty and Profitability on Auditor Change in Various Industrial Sector Manufacturing Companies listed on the Indonesian Stock Exchange. The independent variables in this research are Auditor Opinion, Financial Difficulty and KAP Size. The dependent variable is Auditor Change. The population of this research includes all various industrial companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique used was purposive sampling. The data analysis method used is logistic regression with SPSS version 27. The total sample for this research is 176 companies. The data collection technique uses the documentation method via the official IDX website: www.idx.co.id. The results of this research have implications for accounting knowledge, especially in the field of auditing, by providing empirical evidence regarding the influence of audit opinion, KAP size, financial difficulties and company size on auditor turnover